2010
DOI: 10.1002/mrm.22430
|View full text |Cite
|
Sign up to set email alerts
|

Tracer kinetic analysis of dynamic contrast‐enhanced MRI and CT bladder cancer data: A preliminary comparison to assess the magnitude of water exchange effects

Abstract: The purpose of this study was to determine the impact of water exchange on tracer kinetic parameter estimates derived from T 1 -weighted dynamic contrast-enhanced (DCE)-MRI data using a direct quantitative comparison with DCE-CT. Data were acquired from 12 patients with bladder cancer who underwent DCE-CT followed by DCE-MRI within a week. A two-compartment tracer kinetic model was fitted to the CT data, and two versions of the same model with modifications to account for the fast exchange and no exchange limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 48 publications
3
56
0
Order By: Relevance
“…When dynamic contrast-enhanced MR imaging exchangesensitivity is absent, ⌬ K trans will be effectively zero for both malignant and benign tumors. The results here suggest that data acquisition schemes with decreased exchange-sensitivity ( 41,42 ) would diminish shutter-speed approach breast cancer diagnostic accuracy. protocols, it has been shown that diagnostic accuracies of both standard and shutter-speed approaches decrease substantially ( 45 ).…”
Section: Dynamic Contrast-enhanced Mr Imaging Parametric Mappingmentioning
confidence: 84%
“…When dynamic contrast-enhanced MR imaging exchangesensitivity is absent, ⌬ K trans will be effectively zero for both malignant and benign tumors. The results here suggest that data acquisition schemes with decreased exchange-sensitivity ( 41,42 ) would diminish shutter-speed approach breast cancer diagnostic accuracy. protocols, it has been shown that diagnostic accuracies of both standard and shutter-speed approaches decrease substantially ( 45 ).…”
Section: Dynamic Contrast-enhanced Mr Imaging Parametric Mappingmentioning
confidence: 84%
“…The most common transformation from CA concentration to tissue R 1 is given by Equation 1 [34]: R 1 = r 1 · [ RA ] + R 10 where R 10 is the baseline relaxation of the tissue, [ CA ] is the concentration of the CA in the tissue, and r 1 is the CA-specific relaxivity (in units of mM −1 s −1 ). (We note that Equation 1 is a “fast exchange limit” relation and assumes a linear relationship between CA concentration and R 1 ; for more information on this somewhat controversial point, the interested reader is referred to, e.g., references [35,36,37,38]. We revisit this point in Section 6.)…”
Section: Basic Theory Of Dce-mrimentioning
confidence: 99%
“…As one might guess, the estimated pharmacokinetic parameters may differ significantly [35,161,162,163,164,168] depending on the model that was used to extract them, and these differences may have a significant effect on establishing if, for example, a tumor is responding to treatment. However, there is some disagreement as to whether this formalism is truly justified in a standard DCE-MRI study and it is therefore an active area of investigation [37,38]. …”
Section: Limitationsmentioning
confidence: 99%
“…The PK models are typically refined to more closely reflect physiological processes by including additional parameters, e.g., water exchange and CA diffusion. However, the refinement mostly complicates DCE-MRI analysis, and its usefulness requires additional investigation [197,290,[307][308][309].…”
Section: E Summary and Discussionmentioning
confidence: 99%
“…Classifi-cation of breast tumors by Brix et al [192] was its first DCE-MRI application. Recently, the 2CXM is gradually becoming popular in various applications, such as brain [193,195,287] and lung cancer [288], myometrium [289], cervix [194] and bladder cancer [290], head and neck tumors [291], and carotid atherosclerotic plaques [191].…”
Section: Clinical Applications Of Parametric Modelsmentioning
confidence: 99%